MONITORING OF BUTYLTIN COMPOUNDS IN THE AQUATIC ENVIRONMENTS OF THE PHILIPPINES - Prudente, Maricar S. (Marine Research in Indonesia, 2008)
This article provides a comprehensive review of the contamination by Butyltin compounds (BTs) and its possible implications on the marine and coastal environments of the Philippines. Butyltin compounds were detected in mussels from all the sampling locations investigated as part of the monitoring surveys under the Asia-Pacific Mussel Watch (APMW) Program conducted in the late 1990s. BTs were detected in green mussels collected from all the aquaculture sites in the country, suggestive of considerable widespread pollution by BTs in the coastal waters. Among BTs, TBT was detected at all locations at relatively higher concentrations, whereas the concentrations of DBT and MBT were lower. This could be indicative that green mussels have limited ability of metabolize TBT to DBT and MBT. In addition, this result may be suggestive of fresh TBT inputs into the aquatic environments and the presence of recent sources along the coastal waters. Concentrations of 0 BT in green mussels were reported up to 790 ng/g wet weight in a site where intensive maritime activities are occurring. Mussels from rural areas contained TBT at lower proportions indicating that TBT usage as antifouling agents is minimal. Tolerable average residue level (TARL) for seafood in the Philippines was estimated at 173 ng/g wet weight for an average person weighing 60kg. Concentrations of TBT or the sum of TBT and DBT in some green mussels analysed revealed that some values exceeded TARL level, which could suggest that humans consuming this seafood from areas with high BTs contamination could be at risk from elevated exposure to BTs. Similarly, BTs were detected in all the skipjack tuna collected, suggestive of the widespread contamination even in offshore waters and open seas on a global scale. Skipjack tuna collected from the offshore waters of the Philippines revealed considerable levels (up to 220 ng/g wet weight), with high percentages of BTs in total tin (0Sn: inorganic tin + organic tin) in the liver tissues. This finding seems to suggest that the anthropogenic BTs represent the major source of Sn accumulation in skipjack tuna. On the other hand, relatively low concentrations of BTs were found in the liver of cetaceans from the coastal waters of the Philippines, which ranged 42-98 ng/g wet weight. Significantly lower hepatic BT concentrations in cetaceans in tropical waters were noted compared with those inhabiting temperate waters proximal to developed nations. This result could imply smaller usage of BTs in the Philippines at least at the present.